Comparing the impact of systemic pituitary adenylate-cyclase-activating polypeptide (PACAP) and calcitonin gene-related peptide (CGRP) on motion-induced nausea and balance behaviors in mice - Shafaqat M. Rahman; Abigail Dweh; Anne E. Luebke (PLoS ONE, 2025)
Pituitary adenylate-cyclase-activating polypeptide (PACAP), particularly its dominant isoform PACAP-38, is implicated in migraine and represents a promising therapeutic target. We investigated if intraperitoneally delivered (IP) PACAP-38 impacts motion-induced nausea, postural sway, and imbalance in C57BL/6J wildtype mice using the motion-induced thermoregulation, center of pressure (CoP), rotarod, and balance beam assays. We also assessed systemic Calcitonin Gene-Related Peptide’s (CGRP) effects on these behaviors in parallel. Our findings indicate that IP PACAP-38 significantly disrupts motion-induced thermoregulation in mice, with notable blunting of tail vasodilation responses in both sexes. Additionally, PACAP-38 administration increased postural sway in female mice only and caused balance beam imbalances. Contrary to IP CGRP, IP PACAP-38 did not affect rotarod performance when mice were trained on a dowel with 1.5 cm radius. Our findings provide preclinical evidence supporting a potential role of PACAP-38 in vestibular migraine pathophysiology. Future research will explore if PACAP antagonism can protect against PACAP-38’s effects on nausea and balance behaviors, relevant to treatment of vestibular migraine (VM), especially for patients unresponsive to triptans or CGRP-targeting therapies.